Slab analysis based on stream function method in chamfer edge rolling of ultra-heavy plate. (April 2017) - Ding, JG; Wang, HY; Zhang, DH; Zhao, DW
In this paper, three-dimensional velocity field is proposed by means of stream function method with bisecting yield criterion in chamfer edge rolling of ultra-heavy plate. Parabolic dog-bone shape function is derived so as to obtain velocity field with fixed angle of chamfer edge by stream function method, dog-bone shape coefficient η can be derived from volume invariant condition, and then the plastic deformation power, shear power as well as friction power are obtained respectively with the bisecting yield criterion. Summing up the power contributions, total power functional is presented, from which minimum value can be obtained by searching method, and vertical rolling force and torque are also finally obtained. The predictions of roll force and torque are compared with different angles of chamfer edge as well as different plate thicknesses. The results are shown to be in a very good agreement with the analytical and experimental results.